ANALISIS LAPORAN KEUANGAN BERDASARKAN RASIO LIKUIDITAS, RASIO SOLVABILITAS DAN RASIO RENTABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM BMT EL DANA MANFAAT BANDUNG PERIODE 2017 -2020 - Bahari, Kintan Rizki; Afif, M. Nur; Melani, Maria Magdalena (Jurnal Akuntansi Kompetif, 2024)
A cooperative is a business entity consisting of individuals or legal entities, which carries out its activities by following cooperative principles and functions as a community economic movement that prioritises family principles. Cooperatives are a type of organisation that aims to achieve certain goals in order to meet the interests of its members. Evaluation of the performance of a cooperative or company is carried out to provide a basis for decision making, both by internal and external parties. Evaluation of good financial performance can be done by analysing the results that show a percentage in accordance with predetermined standards. To assess financial performance, a tool or method is needed that allows cooperative management to carry out its duties and responsibilities properly, and in accordance with the objectives of the cooperative in general. The tool used in this analysis is Ratio Analysis, which includes Liquidity Ratio, Solvency Ratio, and Rentability Ratio. This research utilises data from the cooperative's financial statements, including the balance sheet, income statement, and cash flow statement from the period 2017 to 2020, with a quantitative descriptive approach. The analysis technique applied is trend or tendency analysis. Data were collected through survey techniques, which included observation, documentation, and interviews. The purpose of this analysis is to describe or describe the results of the cooperative's financial statements, so as to better evaluate the cooperative's financial performance. Keywords : financial statements, ratio analysis, liquidity ratios, solvency ratios, profitability ratios, and financial performance.